Long-term microstructure and mechanical properties of polymer-phosphazene concrete exposed to freeze-thaw - Tanyildizi, Harun (Elsevier Sci Ltd, 2018)
In this study, the mechanical properties and microstructure of polymer-phosphazene concrete exposed to freeze-thaw was investigated using Anova and Taguchi methods for a period of 1 year. The Taguchi experimental design was used to reduce the number of tests. In the freeze-thaw test, the factors that affect the experimental results were selected as the percentage of phosphazene used in polymer, curing period and cement dosage in the concrete. After the experiment was designed by Taguchi method, 100 x 100 x 100 mm samples were produced. The samples were removed from the water cure at 20 +/- 2 degrees C at the end of 28, 60, 90,180 and 365 days. Then, they dried at 105 +/- 5 degrees C for 24 h. The samples impregnated the polymer containing phosphazene before the freeze-thaw test. Afterwards, these samples were then subjected to a freeze-thaw test. Finally, they were carried out the compressive strength, ultrasonic pulse velocity and weight change experiments. Furthermore, SEM, EDX and XRD analyzes were conducted on the samples. The effects on experimental results of each factor were determined using ANOVA. The results obtained using ANOVA analysis showed that cement dosage had made the most effective parameter. Furthermore, the optimum values for all experiments according to Taguchi method were obtained from polymer-phosphazene concrete produced using the 365 days curing time, 400 kg/m(3) cement dosage and the polymer containing phosphazene 4%. According to these results, the polymer-phosphazene concrete has been resistant to freeze-thaw as it became impermeable. Further, it can be said that other durability properties of the polymer-phosphazene concrete will be good. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Polymer; Phosphazene; Freeze-thaw; Mechanical properties; Microstructure